INVENTARISASI POTENSI BAHAN PAKAN TERNAK RUMINANSIA DI PROVINSI RIAU - Sri Haryani Sitindaon (State Islamic University of Sultan Syarif Kasim Riau, 2013)
The availability of ruminant livestock feed ingredients at region need to be inventoried, which is very important in the development of ruminants. Riau Province has the potential for very large ruminant livestock development, because it is supported by the availability of high local resources. Inventory of material feed for ruminant was conducted to determine the availability of feed resources in Riau Province. Feed materials inventoried in the form of dry matter (DM) included agricultural byproducts (rice straw, corn straw, cassava leaves, sweet potato straw, soybean straw, peanut straw) and plantation byproducts (oil palm fronds and palm leaf, palm kernel cake, coconut cake, cocoa pods) located in 11 districts/cities in Riau Province. Inventory were performed by using primary and secondary data published in 2008. The data obtained were then tabulated based on the conversion rate of Ruminant Livestock Aquaculture Directorate, 2009. The results showed the largest feed ingredients availableis palm kernel cake with DM total of 592,008.57 tons/yr and the lowest was of cocoa pods 145.24 tons/yr. Total availability of DM from all sources of feed ingredients inventoried was 12.253.787,840 tons and could be used to feed ruminant Livestock of about5,237,513.687 AU.